How does retirement affect health? - Evidence from China Health and Retirement Longitudinal Study - Zhao, Ge. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Economics.; Advisor: Marcelo Bianconi.; Keyword: Economics.